Ni, N‐codoped NiMoO4 grown on 3D nickel foam as bifunctional electrocatalysts for hydrogen production in urea‐water electrolysis. (20th September 2021) - Wang, Tuo; Wu, Huimin; Feng, Chuanqi; Ding, Yu; Mei, He
Highlights: l Ni, N-NiMoO4 /NF electrode assembled by micron blocks and nanoparticles. l Superior bifunctional alkaline electrocatalytic urea-water splitting performance. l Ni, N-NiMoO4 /NF-20‖Ni, N-NiMoO4 /NF-20 is superior to Pt/C/NF‖IrO2 /NF. Ni, N-NiMoO4 /NF could be used as two-electrode electrolyzer, the performance electrolysis of urea-water is superior to the water splitting. Abstract: In this study, Ni, N-NiMoO4 /NF, and other compared materials are synthesized as bifunctional electrocatalysts for hydrogen evolution (HER) and urea oxidation reactions (UOR). The results of characterizations and tests show that the electrocatalytic performance of Ni, N-NiMoO4 /NF is higher than those of NiMoO4 xH2 O/NF, Ni-NiMoO4 xH2 O/NF, and N-NiMoO4 /NF, which may be caused by the synergy between Ni, N, and NiMoO4 . The introduction of N and Ni increases the wettability and adsorption of the material, which also increases the conductivity and catalytic performance of the material. Furthermore, it is found that the electrodeposition time of metallic nickel (Ni, N-NiMoO4 /NF-x ( x =10, 20, 30 min)) can affect the catalytic performances of Ni, N-NiMoO4 /NF. The results show that the Ni, N-NiMoO4 /NF-20 shows the best bifunctional electrocatalytic activity among all prepared samples, with 176 mV towards HER and 1.444 V towards UOR at 100 mAcm −2, demonstrating its potential in a practical application as a bifunctional electrocatalyst for hydrogen production in urea-water electrolysis. Graphical abstract: Image, graphical abstract